Lithofacies Association of Fluvial Deposit, Walat Formation in Cibadak Area West Java. Issue 1 (July 2021) - Hafiz, S D; Firman, H; Ramadhan, A; Koesmawardhani, W T
Abstract: Heterogeneities in fluvial sediment sufficiently vary characteristics based on the sedimentology aspect. The sedimentology analysis is the most important parameter to interpret fluvial architecture. Texture variations and sedimentary structures can define and describe where this sediment was deposited. Walat Formation is one of the fluvial deposit is situated in West java. Based on the observation locations that were carried out, it can be seen the outcrop profile, texture, and sedimentary features of this formation. The first observable lithofacies in this area is facies Gm, wherein this facies comprises pebble or cobble gravel with graded bedding, gravel imbrication, and ripple mark. The second one is facies Gp which comprises gravel stratified with planar cross-beds. The third is facies St, medium to very coarse-grained sandstone with laminae and cross-bed. The fourth is facies Sm, which consists of very fine to coarse-grained sandstone with ripple mark and climbing ripple. Furthermore, facies F1 and C comprises interbedded of sandstone, silt shale, and coal with bioturbation, ripple, and undulatory bedding. The fifth, facies Sh which consists of very fine to very coarse sandstone with sedimentary structures is horizontal lamination. The last but not least, facies Ss comprises fine to coarse sandstone with sedimentary structures small scale scours and cross stratification.